A qualitative investigation of organizational, competitive and personal life stressors among amateur athletes - Ponnelle, S.; Berjot, S. (International Journal of Sport Psychology, 2016)
The purpose of this investigation was to identify the most frequent stressors related to sport and non sport domains encountered by a wide range of non-elite French amateur athletes. Ninety athletes of various skill levels took part in semistructured interviews. Qualitative analyses using both inductive and deductive approaches and a frequency analysis were conducted. Eighty two distinct stressors were identified grouped into 25 first-order themes, and 13 second-order-themes, and finally categorized into 4 distinct general dimensions related to sport's organisation, sport's environment, performance accomplishment, and personal life. The proposed classification showed that amateur athletes face common and specific sport-related stressors. The consideration of sport types revealed that while individual sport athletes evocated most often stressors related to the physical environment, to self perception of competence and to nutritional issues, team sport athletes reported more frequently stressors related with competition requirements, leaderships, and interpersonal demands. Limits and directions for future research are discussed.